2018
DOI: 10.1242/jcs.215152
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-dependent cell death – where, how and why a cell eats itself to death

Abstract: Autophagy as a means of cell killing was first advanced by Clark's phenotypic description of 'Type II autophagic cell death' in 1990. However, this phenomenon later came into question, because the presence of autophagosomes in dying cells does not necessarily signify that autophagy is the cause of demise, but rather may reflect the efforts of the cell to prevent it. Resolution of this issue comes from a more careful definition of autophagy-dependent cell death (ADCD) as a regulated cell death that is shown exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
177
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(184 citation statements)
references
References 102 publications
5
177
0
2
Order By: Relevance
“…30 Autophagy acts a key role in cell survival, which is a key pathway for homeostasis, development, and other pathophysiological processes. 31 Moreover, autophagy showed an increase in the expression of autophagy-related proteins such as LC3-II, Beclin-1, and ATG5, with a decrease in the expression of p62. 32 Kinarivala et al 33 reported that the activated Beclin-1 could induce autophagy.…”
Section: Discussionmentioning
confidence: 98%
“…30 Autophagy acts a key role in cell survival, which is a key pathway for homeostasis, development, and other pathophysiological processes. 31 Moreover, autophagy showed an increase in the expression of autophagy-related proteins such as LC3-II, Beclin-1, and ATG5, with a decrease in the expression of p62. 32 Kinarivala et al 33 reported that the activated Beclin-1 could induce autophagy.…”
Section: Discussionmentioning
confidence: 98%
“…This stage of autophagy can be inhibited by chloroquine, hydroxychloroquine and bafilomycin A1 that disturb acidification of the lysosomes ( Figure 2) [55]. The role of autophagy still remains elusive as it can be either a cytoprotective response or followed by induction of different modalities of cell death [60][61][62]. According to the most current recommendations of nomenclature, the term "autophagy-dependent cell death" can be used exclusively when observed cell death is strictly reliant on the autophagic machinery [5,63].…”
Section: An Overview Of Autophagy and Autophagy-dependent Cell Deathmentioning
confidence: 99%
“…post-ischaemic injury, starvation) or chemical (e.g. vintexin treatment) conditions, autophagy can result in autophagic cell death (ACD) [67][68][69]. Typical characteristics of ACD include membrane rupture, numerous autophagolysosomes, and enlargement of major cellular organelles [70][71][72].…”
Section: Autophagic Cell Deathmentioning
confidence: 99%
“…Typical characteristics of ACD include membrane rupture, numerous autophagolysosomes, and enlargement of major cellular organelles [70][71][72]. Mechanistically, ACD is the lethal outcome of disturbed autophagic homoeostasis via excessive self-consumption of cellular content, uncontrolled mitophagy and autosis (Na + /K + -ATP-dependent ACD) [68,69].…”
Section: Autophagic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation